The study of rural tourism policies using the policy Delphi technique – the case of Semporna, Sabah - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Sabah is a premier nature, adventure and cultural destination and is famous for its ecotourism. Tourism in Sabah is one of the three priorities highlighted under the Sabah’s Halatuju Pembangunan dan Kemajuan. Nature tourism has been the main focus area in the tourism policy of the Sabah State Government. The study site, Semporna, is a major tourist attraction in Sabah. The town acts as a place of embankment to the islands such as Sipadan and Mabul. Past research and personal communication indicated that policies pertaining to rural tourism have not reached its full potential. The complexities of the situation are due to the many stakeholders involved in the tourism industry. The scope of this paper will include policy makers, as they comprise one of the five identified stakeholders involved in the tourism industry in Semporna. The objective of this paper is to discuss the Policy Delphi method used to obtain information from the perspective of policy makers. This is found to be the best method to gain insights to policy makers as it ensures anonymity. By ensuring the anonymity, policy makers will be able to express their opinions openly.